Virulence-related factors and antimicrobial resistance in Proteus mirabilis isolated from domestic and stray dogs - Liu, Lijuan; Dong, Zhiyou; Ai, Shengquan; Chen, Shanyu; Dong, Mengyao; Li, Qianlan; Zhou, Ziyao; Liu, Haifeng; Zhong, Zhijun; Ma, Xiaoping; Hu, Yanchun; Ren, Zhihua; et al. (Frontiers in Microbiology, 2023)
Proteus mirabilis is a multi-host pathogen that causes diseases of varying severity in a wide range of mammals, including humans. P. mirabilis is resistant to multiple antibiotics and has acquired the ability to produce expanded spectrum of β-lactamases, leading to serious public health problems. However, the available information on P. mirabilis isolated from feces of dogs, is still poorly understood, as is the correlation between its virulence-associated genes (VAGs) and antibiotic resistance genes (ARGs). In this study, we isolated 75 strains of P. mirabilis from 241 samples, and investigated the swarming motility, biofilm formation, antimicrobial resistance (AMR), distribution of VAGs and ARGs, as well as the presence of class 1, 2 and 3 integrons in these isolates. Our findings suggest a high prevalence of intensive swarming motility and strong biofilm formation ability among P. mirabilis isolates. Isolates were primarily resistant to cefazolin (70.67%) and imipenem (70.67%). These isolates were found to carry ureC, FliL, ireA, zapA, ptA, hpmA, hpmB, pmfA, rsbA, mrpA and ucaA with varying prevalence levels of 100.00%, 100.00%, 100.00%, 98.67%, 98.67%, 90.67%, 90.67%, 90.67%, 90.67%, 89.33% and 70.67%, respectively. Additionally, the isolates were found to carry aac(6')-Ib, qnrD, floR, blaCTX-M, blaCTX-M-2, blaOXA-1, blaTEM, tetA, tetB and tetM with varying prevalence levels of 38.67%, 32.00%, 25.33%, 17.33%, 16.00%, 10.67%, 5.33%, 2.67%, 1.33%, and 1.33%, respectively. Among 40 MDR strains, 14 (35.00%) were found to carry class 1 integrons, 12 (30.00%) strains carried class 2 integrons, while no class 3 integrons was detected. There was a significant positive correlation between the class 1 integrons and three ARGs: blaTEM, blaCTX-M, and blaCTX-M-2. This study revealed that P. mirabilis strains isolated from domestic dogs exhibited a higher prevalence of MDR, and carried fewer VAGs but more ARGs compared to those isolated from stay dogs. Furthermore, a negative correlation was observed between VAGs and ARGs. Given the increasing antimicrobial resistance of P. mirabilis, veterinarians should adopt a prudent approach towards antibiotics administration in dogs to mitigate the emergence and dissemination of MDR strains that pose a potential threat to public health.